2009
DOI: 10.1103/physrevb.80.125414
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure of the liquidAu72Ge28eutectic phase: X-ray reflectivity

Abstract: The surface structure of the liquid phase of the Au 72 Ge 28 eutectic alloy has been measured using resonant and nonresonant x-ray reflectivity and grazing incidence x-ray diffraction. In spite of the significant differences in the surface tension of liquid Ge and Au the Gibbs adsorption enhancement of Ge concentration at the surface is minimal. This is in striking contrast to all the other binary alloys with large differences in the respective surface tensions measured up to date. In addition there is no evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This is manifested in the form of atomic layering normal to the surface that decays within a few atomic distances into the bulk liquid, as was theoretically predicted by D'Evelyn and Rice [1]. Layering was found experimentally in elemental metallic liquids such as, e.g., Ga [2], In [3], Sn, and Bi [4], as well as in liquid alloys such as, e.g., eutectic Bi-Sn [5] and Au-Ge [6]. The atomic arrangement within the topmost layer of most of these liquids is nearly as well defined along the surface normal as those at the surface of crystals.…”
mentioning
confidence: 87%
“…This is manifested in the form of atomic layering normal to the surface that decays within a few atomic distances into the bulk liquid, as was theoretically predicted by D'Evelyn and Rice [1]. Layering was found experimentally in elemental metallic liquids such as, e.g., Ga [2], In [3], Sn, and Bi [4], as well as in liquid alloys such as, e.g., eutectic Bi-Sn [5] and Au-Ge [6]. The atomic arrangement within the topmost layer of most of these liquids is nearly as well defined along the surface normal as those at the surface of crystals.…”
mentioning
confidence: 87%
“…Aside from the surface freezing effect that was observed by Rice 23 There is one difference between the Si and Ge eutectics that suggests a clue to the surface freezing effect. Although Au 82 Si 18 is known to form an amorphous solid phase (i.e., a glass) on rapid cooling 24 the Au 72 Ge 28 liquid does not.…”
mentioning
confidence: 91%
“…This surface layering was first verified experimentally at the liquid-air interfaces of Hg [3] and Ga [4] by x-ray reflectivity (XRR) measurements. Subsequent experimental studies demonstrated such layering also for numerous other liquid metals [4][5][6][7][8][9] and liquid metal alloys [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%